1997
DOI: 10.1097/00002800-199709000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to the Utilization of Nursing Research

Abstract: The nurse in clinical practice must demonstrate a scientific base for practice grounded in research findings. The purpose of this study was to explore the nurse's perception of the barriers and facilitators to using research findings in nursing practice. A survey methodology was used, and a sample of 356 practicing registered nurses responded. Data were collected using a scale that rated the barriers and facilitators to research utilization. The greatest barriers were insufficient time on the job to implement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 11 publications
9
95
1
3
Order By: Relevance
“…It is worth noting that data from the USA, whilst agreeing that these are key barriers, show that a greater proportion of nurses feel competent in these areas. For example, whilst in the UK Dunn et al (1997) found that 70% of nurses felt they were not capable of evaluating the quality of research, in the USA Carroll et al (1997) found this level to be only 51%.…”
Section: Lack Of Skills and Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that data from the USA, whilst agreeing that these are key barriers, show that a greater proportion of nurses feel competent in these areas. For example, whilst in the UK Dunn et al (1997) found that 70% of nurses felt they were not capable of evaluating the quality of research, in the USA Carroll et al (1997) found this level to be only 51%.…”
Section: Lack Of Skills and Knowledgementioning
confidence: 99%
“…Many studies identify the lack of time available to review and implement research findings as a primary barrier to research utilisation. Dunn et al (1997), for example, found that 75% of nurses thought lack of time a great or moderate barrier, Carroll et al (1997) in the USA 71%, Kajermo et al (1998) in Sweden 72%, and Walczak and colleagues, in a small study of oncology nurses in the USA, 85% .…”
Section: Lack Of Support Motivation and Incentives: Nursing 'Culture'mentioning
confidence: 99%
“…Among the 4 commonly studied barriers-innovation (research qualities), communication (research presentation), nurse (adopter), and organization (setting)-the organization has distinctly been perceived as the main impediment. Across the globe, top organizational barriers include limited (1) awareness of research, (2) time to read research and implement new ideas, (3) support from other staff, and (4) authority to change practices. [1][2][3][4][5][6][7][8][9][10][11][12][13] In a qualitative study, 14 a chief organizational barrier was the low priority given to evidence-based practice (EBP) by management.…”
Section: "Inside Looking In" or "Inside Looking Out"? How Leaders Shamentioning
confidence: 99%
“…2,4,5,9 The Promoting Action on Research Implementation in Health Services (PARIHS) framework 15 spotlights the importance of leadership in the use of research in practice. Successful implementation of research is more likely when evidence is scientifically robust, matching professional consensus and patients' preferences; the context is receptive to change with strong leadership and monitoring and feedback systems; and where appropriate facilitation with skilled internal or external facilitators exists.…”
Section: "Inside Looking In" or "Inside Looking Out"? How Leaders Shamentioning
confidence: 99%
“…In the last two decades, scholars from a number of disciplines have described the gap and proposed possible reasons for its existence and continuation (Bhattacharyya, Reeves, & Zwarenstein, 2009;Carroll et al, 1997;Galinsky, Turnbull, Meglin, & Wilner, 1993;Goldfried et al, 2014;Goldfried & Wolfe, 1998;Gray, Sharland, Heinsch, & Schubert, 2014). Although researchers care a great deal about the use of their work and the quality of care clients receive, they also face pressures to produce high-level research and publish.…”
Section: Introductionmentioning
confidence: 99%